Ethanolic stem extract of Excoecaria agallocha induces G1 arrest or apoptosis in human lung cancer cells depending on their p53 status - R. C. Patil (Taiwania, 2012)
Excoecaria agallocha L. is a mangrove widely used as folklore medicine but its anticancer properties have not been evaluated yet. In this study, the ethanol stem extract of this plant exhibited remarkable cytotoxic activities on human lung cancer cell lines in a dose-dependent manner after 48 h of incubation. Analysis of the mechanism of action demonstrated that the extract exerted apoptotic cell death in p53 +/+ cells and G1 arrest in p53-/- cells. Morphological observation using phase-contrast microscope also displayed apoptotic characteristics in treated p53 +/+ cells such as nuclear blebbing and chromatin condensation. Cell cycle analysis showed G1 arrest caused by the extract in p53-/-cells. Furthermore, acute exposure to the extract produced a significant regulation of p21, Bcl-2 and Bax protein expression in both these cell lines. Due to its potent cytotoxic effect on lung cancer cell lines, it is strongly suggested that the extract could be further developed as an anticancer drug.